Peningkatan Prestasi Belajar Bahasa Inggris melalui Penerapan Model Pembelajaran Think Talk Write dengan Metode Diskusi Kelompok Kecil pada Siswa Kelas X A Keperawatan SMK Nusantara Palu - Safiah Safiah (Universitas Tadulako, 2022)
This study aims to determine the increase in student achievement by using the Think Talk Write learning model with the small group discussion method. The subjects in this study were students of class X A Nursing SMK Nusantara Palu, totaling 25 students. This type of research is classroom action research with 2 cycles, each going through the stages of planning, implementing, observing, and reflecting. The instrument used was a test given after the implementation of the Think Talk Write learning model with the small group discussion method. Analysis of the data used is quantitative analysis. The minimum completeness criteria in English subjects is 75. The indicator of success in this study is if classical completeness is 80. The results obtained from this study in the first cycle the average score of students is 60 and classical completeness is 70.23%, the value increases in the second cycle with an average of 80.3 and 84% completeness. From these results, it can be concluded that the Think Talk Write learning model with the small group discussion method can improve student achievement in class X A Nursing at SMK Nusantara Palu in English subjects.